1957
DOI: 10.1152/ajplegacy.1957.191.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate of Chickens as Influenced by Age and Gonadal Hormones

Abstract: The average heart rate of the chick increases from 286 beats/min. at 1 day to 475 at 1 week, with the greatest change occurring during the first 3 days. Heart rate continues to increase slowly to a maximum of approximately 500 beats at 3–4 weeks, then declines gradually to a stable adult level between 280 and 350 at about 6 months. Between the 12th and 17 weeks, the heart rate of the male dropped 10–12% below that of the female, approximating the sex difference found in adults. Heart rate measurements on gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

1960
1960
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
5
13
0
Order By: Relevance
“…While this may have stressed the chicks, the head was free to move and they seemed to be relaxed, closing their eyes from time to time when inspected during preliminary tests. Although the chicks were confined, the HR was determined non-invasively, in contrast with the use of needle electrodes or shaving of plumage as in the ECG recording method (Ringer et al, 1957;Shimada and Koide, 1978). Comparison of the HR found in the present work with that of unrestrained chicks measured in darkness by using electrodes (Shimada and Koide, 1978) seems to indicate no consistent differences, although the variability of HR makes it statistically uncertain.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…While this may have stressed the chicks, the head was free to move and they seemed to be relaxed, closing their eyes from time to time when inspected during preliminary tests. Although the chicks were confined, the HR was determined non-invasively, in contrast with the use of needle electrodes or shaving of plumage as in the ECG recording method (Ringer et al, 1957;Shimada and Koide, 1978). Comparison of the HR found in the present work with that of unrestrained chicks measured in darkness by using electrodes (Shimada and Koide, 1978) seems to indicate no consistent differences, although the variability of HR makes it statistically uncertain.…”
Section: Discussionmentioning
confidence: 54%
“…Comparison of the HR found in the present work with that of unrestrained chicks measured in darkness by using electrodes (Shimada and Koide, 1978) seems to indicate no consistent differences, although the variability of HR makes it statistically uncertain. The HR of chicks, restrained in a supine or prone position, also measured by ECG using needle electrodes (Ringer et al, 1957), increased from 286 bpm on day 1 to 475 bpm on day 7. This increase was much greater than in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…It could be argued that resting f H increased with fish age and therefore masked an underlying negative scaling exponent for f H . However, this possibility is highly unlikely in the light of current knowledge of the effects of ageing on the vertebrate cardiovascular system, where resting f H has been found to remain constant or decrease with adult age (Ringer et al, 1957;Fleg et al, 1995). Also, the blood variables suggested that ageing was not associated with other significant physiological alterations that might change cardiovascular function (e.g.…”
Section: Critique Of Methodsmentioning
confidence: 99%
“…In the White Leghorn, heart rate increases from hatching until around 3 weeks before decreasing until maturity (Ringer et al, 1957;Flick, 1967;Tazawa et al, 1992;Olkowski et al, 1997;. It is possible that heart rates that fail to increase in a bird post-hatch are pathological.…”
Section: Electrocardiographymentioning
confidence: 99%